Parental attitudes towards isiNdebele as a language of learning and teaching in the primary schools in Libangeni Circuit Mpumalanga - Jordaan, Annette Marie (University of Pretoria, 2015)
Mini Dissertation (MA)--University of Pretoria, 2013.